Prevalence, molecular detection and phylogenetic analysis of feline leukaemia virus in peninsular Malaysia - Bande, Faruku (2012)
Feline leukaemia virus (FeLV) is a gammaretrovirus typically associated with the development of lymphoma, anaemia and immunodeficiency in cats. A cross sectional survey was carried out from January 2010 to December 2010 to determine the prevalence and risk factors associated with FeLV infection in Peninsular Malaysia. A total of 368 cats were screened for the presence of FeLV p27 antigen and information on cat‟s demography as well as health status were obtained and analysed by logistic regression for their association with the risk of FeLV infection. The overall prevalence of FeLV was found to be 12.2% (45/368). Prevalence was higher among sick cats (18.9%) compared to healthy cats (5.1%) and in client-owned cats (13.1%) compared to shelter cats (10.3%). Logistic regression analysis revealed that male gender, young age, aggressive behaviour, sickness, living in multi-cat household or shelter environment significantly increased the risk of FeLV positivity. Thus, cats under these categories are likely at higher risk of developing FeLV associated conditions and possibly play a role in shedding the virus to other naïve cats. Higher prevalence of FeLV observed in this study suggests the need for specific control measures such as screening and vaccination to ensure that FeLV infection is controlled among cats in Peninsular Malaysia. In a follow-up study, a highly sensitive nested PCR assay was optimized and used to detect the presence of FeLV viral RNA and provirus DNA from the plasma and blood samples respectively. Comparison was made between p27 antigen test and nested RT-PCR assay. In FeLV viral RNA detection, a total of 78 cats comprising up of an equal number of p27 antigen positive and p27 antigen negative cats were evaluated. Viral RNA was detected in 87.2% (35/39) p27 antigen positive and 12.8% p27 seronegative cats respectively. A substantial agreement was observed between p27 antigen detection test and nested RT-PCR assay (κ = 0.74). On the other hand, when nested PCR assay was used to determine FeLV proviral DNA status of 39 p27 antigen negative cats, about 97.4% (38/39) of p27 antigen negative cats were found positive for FeLV proviral DNA. Detection of FeLV viral RNA and Proviral DNA among antigen positive and antigen negative cats suggest that both persistent and latent FeLV infections are prevalent among cats in Peninsular Malaysia. Although substantial agreement was recorded between p27 antigen test and nested RT-PCR assay, nested RT-PCR was shown to offer additional advantage as it was able to detect viral RNA in 12.8% antigen negative cats. Cats that were tested negative for FeLV antigen but provirus DNA positive are likely to go undetected when only antigen detection assays are considered for the diagnosis of FeLV. Thus, combination of both p27 antigen detection test and PCR assays will provide better understanding of FeLV infection status of cats. To gain further insight into Malaysian FeLV genotypic variation, 29 nested PCR positive samples were selected, sequenced and subjected to multiple sequence alignment and phylogenetic analysis. Malaysian FeLV samples were shown to exhibit higher sequence homology ranging from 91-100%. When compared with the reference FeLV isolates,Malaysian FeLV had highly conserved sequence variation that reduces up to 84%. Phylogenetic analysis further revealed that local FeLV sequences were group in two distinct clusters. The majority of local FeLV samples (86%) clustered together with FeLV-K01803 which is a member of FeLV-B subgroup from UK, while the remaining samples (14%) were grouped with FeLV-GM1 isolate which is also a member of subgroup B. This might suggest that FeLV-B is likely the most predominant sub-group occurring in Peninsular Malaysia. In overall, this study has provided valuable information on the epidemiology of FeLV in both client-owned and shelter cat population in Malaysia. Additionally, the study provided the first molecular-based FeLV study in Malaysia; highlighted the significance of using PCR assay as a diagnostic tool for evaluating FeLV infection status and one of the few Genebank representations of FeLV sequences from South East Asian region. Future studies should be directed toward isolation and adaptation of FeLV in cell culture, whole genome sequencing and vaccine efficacy studies so as to further understand the molecular characteristics, immune response and pathogenesis of local FeLV isolates.